Long pentraxin 3 (PTX3) regulates IL-17A-mediated immunity to Leishmania major infection in mice - Gupta, Gaurav; Mou, Zhirong; Jia, Ping; Onyilagha, Chukwunonso; Shan, Lianyu; Soussi-Gounni, Abdelilah; Uzonna, Jude E. (Frontiers in Immunology, 2026)
Cutaneous leishmaniasis, caused by protozoan parasites of the Leishmania genus, remains a significant health concern in endemic regions such as the Middle-East, Asia, Latin America, and North Africa. The disease affects millions of people worldwide, with over one million new infections reported annually. Despite its health impact, there is currently no approved vaccine largely due to limited understanding of immunological mechanisms underlying protective immunity and disease pathogenesis. We previously reported that long pentraxin 3 (PTX3), a pattern recognition molecule involved in inflammation, tissue repair, and wound healing, is a negative regulator of immunity in primary Leishmania major infection. Specifically, we showed that PTX3 exacerbates disease by suppressing protective Th17 responses. Here, we extend these findings by showing that PTX3 also influences secondary (memory) immunity to L. major. PTX3-deficient (PTX3-/-) mice which had resolved a primary infection exhibited enhanced resistance to secondary challenge compared to their wild-type (WT) controls. This enhanced resistance correlated with higher frequencies of effector memory CD4+ T cells in the spleens and draining lymph nodes. Upon re-infection, healed PTX3-/- mice produced significantly more IL-17A, while levels of IFN-γ, TNF-α, and IL-10 were similar. In vivo BrdU incorporation assays further revealed increased proliferation of IL-17+ CD4+ T cells in PTX3-/- mice. Importantly, neutralization of IL-17A during secondary challenge abolished the enhanced resistance observed in PTX3-/- mice, confirming a central role of IL-17 in PTX3-regulated secondary immunity. Collectively, our findings identify PTX3 as a key regulator of secondary immunity in cutaneous leishmaniasis and underscores the importance of IL-17 in this process.